1997
DOI: 10.1111/j.1939-1668.1997.tb00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Eero Saarinen's Firestone Baars Chapel: Poetics of a Sacred Place

Abstract: OBJECTIVEThe objectives of this criticism are to provide a brief history and description of the Chapel, review the coincidence between expression and interpretation through functionalist and formalist approaches, make conjectures about the origin of the Chapel's interior, and draw conclusions about the poetic qualities of the Chapel's humanistically conceived space.The above objectives are met by reviewing original archival material, conducting on-site observations, interviewing current and retired faculty, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This study also borrowed from Schwarz and Brent (1997) who critiqued Saarinen's Firestone Baars Chapel partially through the lens of functionalism. Acknowledging that the critic is not fully capable of interpreting the designer's original intent, later observation and understanding relies on an assessment of how a structure performs based on programmatic intent.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…This study also borrowed from Schwarz and Brent (1997) who critiqued Saarinen's Firestone Baars Chapel partially through the lens of functionalism. Acknowledging that the critic is not fully capable of interpreting the designer's original intent, later observation and understanding relies on an assessment of how a structure performs based on programmatic intent.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Acknowledging that the critic is not fully capable of interpreting the designer's original intent, later observation and understanding relies on an assessment of how a structure performs based on programmatic intent. In this earlier case study, Schwarz and Brent (1997) built on the work of Mitchell (1990) who suggested "a description of form tells what an object is, while a functional description tells what it accomplishes" (p. 183). Furthermore, Mitchell (1990) pointed out that context matters, and the functional description of architecture may change over time as the context in which it exists shifts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations